DIGITAL TRANSFORMATION THE FIRST STEPS OF VOICE OF VIETNAM (VOV) - Dong Manh Hung; Tran Huong Tra (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Since its inception over a century ago, radio has proven to be one of humanity's most advantageous media. Radio has been modified to better serve the public as a result of the current technology revolution. The costs of starting a radio station with vast coverage are greatly decreased thanks to Internet broadcasting and streaming. The public can now readily listen to and even "watch" radio broadcasts from stations all over the world thanks to mobile phones and smartphones. On September 7, 1945, the Voice of Vietnam (VOV) was founded. The Voice of Vietnam has endeavored to approach and implement new technical technologies for broadcasting and production activities since its foundation. It is digitizing its production and broadcasting at the moment. This has not only made radio production faster but also more accessible to a wider audience...The following article discusses VOV's digital transformation, which aims to improve services for the public.